Masculinity Values in The Glass Menagerie - nensia nensia nensia (Hasanuddin University, 2020)
Masculinity is the labeling for men related to sex, identity, responsibility, culture, tradition, and others aspect. Masculinity is also the term of separating position for men from female. The aim of the research was to describe the masculinity values of the men characters in the drama whose name is Tom that he is depressed by his mother. The research employed a descriptive qualitative method with structuralism approach. Data sources were primary and supporting data. The primary data were taken from Tennessee William’s The Glass Menagerie, and supporting data were taken from the books, journals, articles, and internet sources. The research indicated masculinity values in this drama had shown man’s role as a son, man as an independent man, and man as a friend.